Essential tools for deep learning and data science. (Manning Publications, 2020)
Learn the most important tools in the repertoire of a data scientist and machine learning practitioner - Principal Component Analysis (PCA), Singular Value Decomposition (SVD), and Latent Semantic Analysis (LSA) - with the help of Krishnendu Chaudhury, a deep learning and computer vision expert with decade-long stints at both Google and Adobe Systems.